The Impact of Digital Transformation on Business Models: A Bibliometric Study - Judijanto, Loso (The Eastasouth Management and Business, 2025)
This study explores the impact of digital transformation on business models through a bibliometric analysis of research indexed in the Scopus database, utilizing VOSviewer for data visualization. The analysis identifies "digital transformation" as a central theme, closely linked to emerging technologies such as artificial intelligence, big data, blockchain, and IoT, which are driving innovation and reshaping traditional business practices. Key research clusters highlight themes of strategic alignment, data-driven decision-making, and technological infrastructure as critical enablers of transformation. Additionally, sustainability and economic inclusivity emerge as new areas of focus, emphasizing the broader societal implications of digital transformation. Geographic and collaborative patterns reveal strong contributions from countries like the United States, China, and Germany, underscoring the global and interdisciplinary nature of the research. Despite the progress, challenges such as cybersecurity, cultural adaptation, and long-term resilience remain underexplored, offering directions for future research. This study provides valuable insights for academics and practitioners seeking to navigate the evolving landscape of digital transformation and business model innovation.